What doesn't kill her - Dodd, Christina (Cape Charade, 2019)
"One secret, one nightmare, one lie. You guess which is which. 1. I have the scar of a gunshot wound on my forehead. 2. I have willfully misrepresented my identity to the US military. 3. I'm the new mother of a seven-year-old girl. Kellen Adams suffers from a yearlong gap in her memory. A bullet to the brain will cause that. But she's discovering the truth, and what she learns changes her life, her confidence and her very self. She finds herself in the wilderness, on the run, unprepared, her enemies unknown--and she is carrying a priceless burden she must protect at all costs. The consequences of failure would break her. And Kellen Adams does not break. What doesn't kill her...had better start running"--